Silicon bioceramic loaded with vancomycin stimulates bone tissue regeneration. Issue 6 (3rd November 2017) - Manchón, Angel; Alkhraisat, Mohammad H.; Rueda‐Rodriguez, Carmen; Pintado, Concepción; Prados‐Frutos, J.C.; Torres, Jesus; Lopez Cabarcos, Enrique
Abstract: Porous ceramics doped with silicon and pure β‐TCP were analyzed in terms of internal microstructure, cell behavior, and the percentage of newly formed bone. Additionally the materials were tested to determine which of the two had better properties to load and release vancomycin hydrochloride. Internal pore distribution and porosity were determined through high pressure mercury porosimetry and the specific surface area was measured by the Brunauer Emmet‐Teller method. The proliferation and viability of the human osteoblast‐like cell line MG‐63 was studied to validate both materials. The materials were tested on eight New Zealand rabbits which created defects, 10 mm in diameter, in the calvaria bone. After 8 and 12 weeks a histological and histomorphometric analysis was performed. Si‐β‐TCP showed a higher porosity and specific surface area. The cytocompatibility test revealed acceptable results in terms of proliferation and viability whereas the percentage of new bone was higher in Si‐β‐TCP with a two‐time study being statistically significant with 12 weeks of healing ( p  < 0.05).The vancomycin loaded within the ceramic scaffolds were burst released and the material had the ability to inhibit bacterial growth. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2307–2315, 2018.